(untitled) (REMUNOM, 2026)
Considering that transfusion safety directly depends on donor–recipient compatibility, this study addressed the need to understand the clinical importance of erythrocyte phenotyping within the ABO and RhD systems. Objective: To identify the main deterministic factors that demonstrate the relevance of this practice as an essential tool for preventing alloimmunization and adverse transfusion reactions. Methodology: An integrative literature review with comparative analysis of the findings is carried out, based on articles published between 2020 and 2025 in the SciELO and PubMed databases. Results: Seventeen studies were selected, revealing that the systematic application of erythrocyte phenotyping significantly reduces the risk of incompatibilities, improves blood stock management, and strengthens hemovigilance policies. Conclusion: Erythrocyte phenotyping is an indispensable tool for transfusion safety and for achieving more precise, ethical, and humanized clinical practice.